Isolation and characterization of bacillus species from soil in Ngere tea catchment area of Murang’a county, Kenya - Wafula, Eliud N.; Kinyua, J.; Karuiki, D.; Muigai, A.; Mwirichia, Romano K. (My University, 2014)
Bacteria are a very diverse group of organisms in soil, and major taxonomic groups are represented in most soils. The extent of the diversity of microorganisms in soil is seen to be critical to the maintenance of soil health and quality, since a wide range of bacteria are involved in the important soil functions. The objectives of this study were to isolate, characterise and identify groups of bacteria from Bacillus species that are associated with soil quality in tea growing areas of Ngere. 10 isolates were obtained using dilute nutrient broth agar and the bacterial morphology was identified as gram-positive rod-shaped bacteria, they grew well at pH ranging from 5 6.5 and temperature range of 25o C 35o C. Based on different biochemical tests and sequence of 16S rDNA, the isolated bacteria were identified as belonging to genus Bacillus. Phylogenetic analysis of isolates D61, D19, and, D51, suggested that they were closely related to Bacillus cereus with 89-96% rDNA sequence analysis similarity while isolates D5, D16, S31, D70 and D2 were closely related to Bacillus thuringiensis with 83% - 96% rDNA sequence analysis similarity. Isolate S30 was closely related to Bacillus subtilis with 99% rDNA sequence analysis similarity and isolate D29 was closely related to Bacillus mycoides with 97% rDNA sequence analysis similarity. Given the low similarity values some isolates had to their closest relatives, chances are high that Ngere tea catchment area harbours a diverse population of as yet, uncultured and uncharacterized microbes.
Isolation and characterization of bacillus species from soil in Ngere tea catchment area of Murang’a county, Kenya
Keywords: Soil quality; Tea; Bacteria; Phylogenetic analysis and Bacillus species